The Validity of Cloze Test in Measuring Reading Comprehension of The Students : Case Study SMP Swasta Bharlind School Medan - Enike Sandry (Cendikia : Media Jurnal Ilmiah Pendidikan, 2021)
This study deals with validity of cloze test in measuring reading comprehension. The objectives are to find out cloze test of fixed or variable deletion a valid measure of reading comprehension, and to find out to which level of reading comprehension is cloze test most valid. This was an export facto quantitative study. In this study, the writer took 40 students at SMP Swasta Bharlind School Medan, as the sample and they were divided into two grows. There are six hypotheses in this study in order to answer the research problems. Cloze test and TOEFL test were used as the instrument for collecting the data. The findings were that cloze test using fixed-ratio method significantly correlate with reading comprehension of TOEFL and also with literal and inferential comprehension items of TOEFL in measuring reading comprehension. And the cloze test using variable-ratio method significantly correlate with reading comprehension of TOEFL but doesn’t significantly correlate with both literal and inferential comprehension items of TOEFL in measuring reading comprehension. Then, cloze test using fixed-ratio method is a valid measure of reading comprehension (0,77), while cloze test using variable-ratio method is not a valid measure reading comprehension (0,69). Mean while cloze test using variable-ratio method does not significantly correlate with inferential comprehension items of TOEFL in measuring reading comprehension.